Canine and feline papillomaviruses: an update - Medeiros-Fonseca, Beatriz; Faustino-Rocha, Ana I.; Medeiros, Rui; Oliveira, Paula A.; Gil da Costa, Rui M. (Frontiers in Veterinary Science, 2023)
Papillomaviruses are small viruses able to cause disease not only in mammalians, but also in birds and reptiles. In recent years, a rising number of papillomaviruses have been identified in dogs and cats, totaling twenty-four canine papillomavirus (CPV) and six feline papillomavirus (FcaPV). The canine and feline papillomaviruses (CPVs and FcaPVs, respectively) are responsible for multiple lesions in these domestic species but the potential pathological relevance of some recently identified types remains to be determined. CPVs are associated with oral papillomatosis, cutaneous papillomas and viral pigmented plaques, and have been rarely associated with the development of oral and cutaneous squamous cell carcinomas in their canine hosts. FcaPVs are associated with oral papillomas, viral plaques, and Bowenoid in situ carcinomas. The present review provides readers with the more recent advances on dog and cat papillomavirus research, bringing an update on this field to both veterinary practitioners and the virology community at large.